SLMs for Natural Language database interaction with the SENSE Citiverse of Cartagena City - Carmona-Martínez, Alejandro; Jara, Antonio; Molina, Germán (Street Art & Urban Creativity, 2025)
European data spaces host rich catalogues yet rarely turn data into timely answers. We present a self‑contained Natural Language data assistant for Cartagena’s SENSE Citiverse. It orchestrates three SLMs (Entities, SQL, and Domain Expert) on DataHub, Trino and KServe/Kubeflow stack. Two SLM stacks (Compact, Expanded) were evaluated on six air‑quality and port‑operations tasks against Gemini 2.5-Pro LLM. Entity extraction achieved perfect table-discovery. SQL solved 4/6 (Compact) and 5/6 (Expanded); Gemini solved 6/6. The SLM design preserves data-sovereignty and reduces cost. This work demonstrates a new way to interact in the Citiverse based on Natural Language.